1998
DOI: 10.1093/oxfordjournals.molbev.a025919
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species in marine polychaete and their independent introduction from North America to Europe

Abstract: The vast body of ballast water carried across oceans by freight ships represents a major source for the introduction of foreign species into marine ecosystems. The worm Marenzelleria viridis, originally found only in North America, appeared in estuaries of the North Sea in 1979 and 6 years later also in the Baltic, where it has developed into a major faunal element. Two competing hypotheses are discussed here: either both populations owe their presence to a single introductory event in the North Sea, or each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 20 publications
1
76
0
1
Order By: Relevance
“…Studies of geographic range and life history may overlook patterns of diversity and underlying evolutionary processes, particularly in diverse marine communities where barriers to gene flow are not readily apparent (Palumbi 1994;Bastrop et al 1998;Knowlton 2000;Rocha-Olivares et al 2001;Hebert et al 2003a). Estuaries are excellent systems with which to address this issue, though studies have failed to explicitly identify the geographic background against which this might occur (Bilton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of geographic range and life history may overlook patterns of diversity and underlying evolutionary processes, particularly in diverse marine communities where barriers to gene flow are not readily apparent (Palumbi 1994;Bastrop et al 1998;Knowlton 2000;Rocha-Olivares et al 2001;Hebert et al 2003a). Estuaries are excellent systems with which to address this issue, though studies have failed to explicitly identify the geographic background against which this might occur (Bilton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…3) with the break occurring across Cape Hatteras, where steep temperature gradients and currents converge at the Virginian and Carolinian provincial boundaries (Palumbi 1994; Engle and Summers 1999). Here, breaks or range point ends in other species are linked to dispersal ability and the physical conditions (Saunders et al 1986;Bastrop et al 1998;Jones and Quattro 1999;Collin 2001), which likely preclude gene flow through vicariance or selection (Palumbi 1994;Sotka et al 2004;Stevens and Hogg 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the actual number of invaders and the impacts of these species may be underestimated because of the presence of cryptic invaders, or species that cannot be easily classified as native or introduced (3). Over the past decade, use of PCR-based molecular techniques have revealed repeated occurrences of such invasions in marine ecosystems (4)(5)(6), and studies have demonstrated both genetic and physiological differences between invading and native populations (6). Given that cryptic invaders typically are unrecognized or are mistaken for native species, knowledge of historical trends in geographic distribution and population genetic structure in cases of suspected introductions are of particular interest when trying to reconstruct the invasion history of a species.…”
mentioning
confidence: 99%
“…Many examples of cryptic differentiation have been revealed by molecular techniques in polychaetes (Bastrop et al 1998, Westheide & Hass-Cordes 2001, Jolly et al 2004, Audzijonyte et al 2008, Virgilio et al 2009). …”
Section: Introductionmentioning
confidence: 99%